Preliminary Definitions for the Sonographic Features of Synovitis in Children. Issue 8 (August 2017) - Roth, Johannes; Ravagnani, Viviana; Backhaus, Marina; Balint, Peter; Bruns, Alessandra; Bruyn, George A.; Collado, Paz; De la Cruz, Lorenia; Guillaume‐Czitrom, Severine; Herlin, Troels; Hernandez, Cristina; Iagnocco, Annamaria; et al.
Abstract : Objective: Musculoskeletal ultrasonography (US) has the potential to be an important tool in the assessment of disease activity in childhood arthritides. To assess pathology, clear definitions for synovitis need to be developed first. The aim of this study was to develop and validate these definitions through an international consensus process. Methods: The decision on which US techniques to use and the components to be included in the definitions, as well as the final wording, were developed by 31 US experts in a consensus process. A Likert scale of 1–5 (where 1 = complete disagreement and 5 = complete agreement) was used. A minimum of 80% of the experts scoring 4 or 5 was required for final approval. The definitions were then validated on 120 standardized US images of the wrist, metacarpophalangeal joints, and tibiotalar joints, displaying various degrees of synovitis at various ages. Results: B‐mode and Doppler should be used for assessing synovitis in children. A US definition of the various components (i.e., synovial hypertrophy, effusion, and Doppler signal within the synovium) was developed. The definition was validated on still images with a median of 89% of participants (range 80–100) scoring it as 4 or 5 on a Likert scale. Conclusion: US definitions of synovitis and its elementary components covering the entire pediatric age range were successfully developed through a Delphi process and validated in a web‐based still‐images exercise. These results provide the basis for the standardized US assessment of synovitis in clinical practice and research.